Pengolahan Lindi TPA Muara Fajar Pekanbaru Menggunakan Sequencing Batch Reactor Aerob dengan Variasi Teknik Stabilisasi (IDLE) - Ashari Syawal, Ferdy; Dinil Fitri, Shafira; Darmayanti, Lita; Andrio, David; Tanjung, Munir; Fadhila, Fadhila (Jurnal Teknik Kimia USU, 2026)
Leachate is a liquid generated from waste decomposition containing organic matter, ammonia, heavy metals, and suspended solids in high concentrations. Improper leachate disposal can pollute soil and water around the landfill. This study aims to determine the effect of different idle stabilization techniques on COD, ammonia, and TSS removal efficiency using an aerobic Sequencing Batch Reactor (SBR). Three idle variations were tested: static idle, mixed idle, and aerated idle. The SBR reactor was operated with fill (1 h), react (18 h), settle (2 h), draw (1 h), and idle (2 h) phases for four cycles. The results showed that the aerated idle variation achieved the highest removal efficiencies: COD 86.67%, ammonia 95.36%, and TSS 93.97%. Aerated idle provided better sludge stability and optimal oxygen conditions for microbial activity.